Synthesis of CdIn2Se4and Cu0.5Ag1.5InSe3compounds via chemical and solid-State methods - Viratchara Laokawee (2018)
CdIn2Se4and Cu0.5Ag1.5InSe3are high-performance thermoelectric materials. In this study, both CdIn2Se4and Cu0.5Ag1.5InSe3powders were synthesized using a microwave and solution method followed by annealing in nitrogen atmosphere. CdIn2Se4was synthesized by two routes. First, CdSe was prepared using a microwave method. Second, In metal was prepared using a solution method. The prepared metals were annealed in nitrogen atmosphere. From the x-ray diffraction (XRD) results, CdIn2Se4was observed as the main phase with CdSe and In2O3as contaminant phases. The synthesis of Cu0.5Ag1.5InSe3was also divided into two steps. First, CuAg and Se were prepared using a microwave method. Second, In metal was prepared using a solution method. The prepared metals were annealed in nitrogen atmosphere. From the XRD results, Cu0.5Ag1.5InSe3was observed as the main phase with Cu0.5-xAg1.5-yInx+ySe and Se as contaminant phases. © 2014 TMS.